(untitled) (Journal of Ideas in Health, 2021)
Background: The present study examines the relationship between resilience, mood, fear for Covid-19, and cognitive functioning during pandemic Covid-19. Methods: A cross-sectional web-based study was conducted from December 2020 to January 2021 among the administrative staff of the University of Western Macedonia, Greece. Data was collected using the Connor-Davidson Resilience Scale (CD-RISC), Depression, Anxiety, and Stress (DASS 21), fear of Covid-19 scales (FCV-19S), and Cognitive functioning self-assessment scale (CFSS). Univariate, bivariate, and multivariate analysis was performed using an independent Sample T-Test, Chi-Square Test, One-way ANOVA, Mann-Whitney U Test, Kruskal-Wallis H Test, Spearman’s Rank-Order Correlations, Pearson product-moment correlations, and Simple Linear Regression. SPSS version 22 was used for data analysis and the statistical significance was considered at less than 0.05. Results: Data of 88 university’s administrative staff has undergone final analysis. Most of the respondents were females (78.4%), married (61.3%), middle-aged group (64.8%), held a post-graduate degree (56.8%) and 94.3% stated that they had not been sick with Covid-19. Our findings showed that the middle-aged group has statistically significantly higher fear on Covid-19 (P = 0.046), and more care of personal hygiene, stress (P = 0.040), than the young age group respectively. Women had a statistically significantly higher restriction to physical contact compared to men (P = 0.042), however, men had statistically significantly more trusted the results of clinical trials of Covid-19 vaccines than women (P = 0.039), respectively. There was statistically significant and negative correlation between Resilience (CD) and cognitive functioning (r = -0.412, n = 87, P < 0.001). Furthermore, the result of a simple linear regression showed that an increase of one in CD corresponded to a 0.287 decrease in cognitive functioning. Conclusion: It is vital to continue monitoring the psychological and cognitive effects of the Covid-19 pandemic.